Prevalence and Antimicrobial Resistance of Salmonella Isolated From Dead-in-Shell Chicken Embryos in Shandong, China - Zhao, Xiaonan; Ju, Zijing; Wang, Guisheng; Yang, Jie; Wang, Fangkun; Tang, Hui; Zhao, Xiaomin; Sun, Shuhong (Frontiers in Veterinary Science, 2021)
The present study was designed to explore the Salmonella prevalence and antimicrobial resistance characteristics in the context of chick mortality at hatching in China. Between December 2015 and August 2017, 1288 dead-in-shell chicken embryos were collected from four breeder chicken hatcheries in Tai’an, Rizhao, Jining, and Heze, China. Salmonella isolates were successfully recovered from 6.7% of these embryos (86/1288), and were evaluated for serotype, antimicrobial susceptibility, Class 1 integron prevalence, antimicrobial resistance gene expression, and multilocus sequence typing (MLST). Salmonella Thompson (37.2%), and Salmonella Infantis (32.6%) were the two most prevalent isolates in these chicken embryos, and 66.3% of isolates exhibited robust ampicillin resistance, while 55.8% of isolates exhibited multi-drug resistance (MDR). The majority of isolates harbored the blaTEM gene (74.4%), with the qnrS gene also being highly prevalent (50.0%). In contrast, just 27.9% of these isolates carried Class 1 integrons. These 86 isolates were separated into four sequence types (STs), whereby ST26 (32.2%) was the most prevalent. Overall, these results suggested that Salmonella infections may be an important cause of chicken embryo mortality in China, and that efforts to support the appropriate use of antibiotics in managing poultry populations are essential.